Choriocarcinoma associated with ectopic pregnancy. A case report - Manandhar, Tara; Upreti, Rakchya; Sitaula, Sarita (Birat Journal of Health Sciences, 2020)
Choriocarcinoma is an uncommon malignant neoplasia and even rarer is the Choriocarcinoma associated with ectopic pregnancy. Here, we present a case of Choriocarcinoma in a young lady who had undergone laparoscopic salphingectomy for rupture ectopic pregnancy, and presenting after 2month in hemorrhagic shock requiring urgent laparotomy.